Maternal Age and Offspring Human Capital in India - Marcello Perez Alvarez; Marta Favara (ZBW - Leibniz Information Centre for Economics, 2020)
The consequences of early motherhood for the offspring are severely understudied, especially in low- and middle-income countries, where this phenomenon is prevalent. Using panel data from India, this paper investigates the effect of early maternal age on offspring human capital in terms of health and cognition. The analysis relies on mother fixed effects to allow for mother unobserved heterogeneity and explores for the first time the evolution of effects over time, covering the offspring phases of childhood and early adolescence. Our results indicate that children born to early mothers are shorter for their age and perform poorer in the math test, with stronger effects for (female) offspring born to very young mothers. Interestingly, the Adolescent Motherhood, Human Capital, Child Development, Cognition, Health, Nutrition, Gender, Parenting effect on health weakens over time, while the cognition effect surges in early adolescence. Further analysis suggests both biological and behavioral factors as transmission channels.
Keywords: I15; I25; J13; J16; O15; 330; Adolescent Motherhood; Human Capital; Child Development; Cognition; Health; Nutrition; Gender; Parenting